Intervensi Keperawatan “Peningkatan Tidur“ pada Pasien Gagal Jantung dengan Gangguan Tidur: Laporan Kasus - Agus Joko Purwanto; Elly Nurrachmah; Prima Agustia Nova; Suko Basuki (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to describe nursing interventions to improve sleep in heart failure patients with sleep disorders. This research is a case report of nursing intervention. The results of the study obtained a case report discussing the case of a 65-year-old man with heart failure who had trouble sleeping, was restless and his condition was getting worse. The nursing diagnosis that emerged was sleep disturbance, with the expected outcome: sleep, and the nursing intervention was sleep improvement. In conclusion, the application of nursing interventions to improve sleep results in a better outcome in overcoming the problem of sleep disorders in heart failure patients. Keywords: Heart Failure, Sleep Disorders, Case Reports, Sleep Improvement